"[This] system was not made for [you]:" A case for decolonial Scientia. Issue 2 (31st December 2020) - Watkins, Rachel J.
Abstract: Background: Sylvia Wynter's "recoded" form of science called decolonial Scientia (DS) is grounded in an understanding of humans as simultaneously biological and cultural. DS includes narrative interventions that destabilize Western scientific authority, and address limitations that empirical data collection and analysis place on capturing simultaneous realities. Therefore, Wynter's narrative "languaging" is both scientific critique and grounded in a tradition of Black radical imagining. Aims: In this article, I use languaging to destabilize the canonical narrative tied to W. M. Cobb's production of the article "Race and Runners." The standard telling focuses on Cobb's examination of Owens' lower extremities to expose the fallacy of racial differences in athletic ability. Destabilization of the narrative allows for identifying relational complexities between actors involved in the canonical story – and identifying ideologies embedded within it that guide our deconstructions of biological race. My alter(ed)native subjectivity informs my use of languaging to argue that the relationship between narrative and research practices belie Western scientific/unscientific binaries. Materials and methods: Audiovisual and documentary sources of the public‐facing "Race and Runners" story were subject to comparative analysis to verify the content and order of events in the canonical narrative. Letters focused on race and athletic ability obtained from the W. Montague Cobb Manuscript Collection at Howard University serve as "apocryphal" sources of information. Correspondence between Cobb and a representative member of the public named Howard Duncan took place within a period immediately before, during and after Cobb publishes "Race and Runners" in the Journal of Health and Physical Education. Contents were subject to a systematic analysis that involved reviewing documents to identify statements reflecting scientific practices, human interactions and relationships between race and athletic ability reflected in the canonical narrative. Contents were also examined for statements relevant to the narrative that departed from or added to the canonical story in the same three areas. Details regarding departures and additions were recorded along with the specific part of the narrative to which they corresponded. Narrative departures and additions were articulated with the canonical narrative in the interest of destabilizing it to identify "knots of ideas, histories and narratives that, contrary to Western science, can only be legible in relation to one another" (McKittrick, 2015b p. 2). Results: Letters exchanged between Cobb and Duncan reveal dynamics that are obscured in the canonical storyline. For instance, Duncan's ability as a white male to assert himself as Cobb's peer demonstrates how racialized power is enacted through science. This is also reflected in Owens' position in the narrative as a voiceless object of knowledge. Letters also present Cobb's identity beyond being a "pioneer, " rendering how he is studying and experiencing racism. This includes how he refuses to engage Duncan as a peer. Discussion: More than mere stories, narratives are motivating and instructive forces that shape how we study human biology and use our research to oppose biological notions of race. Correspondence between Cobb and Duncan reveals how Western scientific ideologies that reinforce prescribed roles and boundaries are embedded in narratives. These ideologies can limit the transformative potential of our approaches to contesting biological notions of race. Abstract : Special Issue: Race reconciled II: Interpreting and communicating biological variation and race in 2021